Mass Spectrometric Studies of Positive Ion/Molecule Reactions in NH3 and SF6 Gases - Talib, Zainal Abidin; Saporoschenk, M (1992)
Positive ion-molecule reactions in NH] and SF6 gas were studied in a static ion drift-tube mass spectrometer. E/N (the ratio of electric field strength to gas number density) varied typically from 20-400 Td and pressure ranged from 0.1 to 0.8 Torr. The most important process was found to be